A configurational analysis of board involvement in intergovernmental organizations. (28th May 2018) - Federo, Ryan; Saz‐Carranza, Angel
Abstract: Manuscript Type: Empirical Research Issue: Research on board involvement has evolved and shifted towards seeking the appropriate role these boards should play in the strategy process. Current theoretical debates and inconclusive empirical findings in the literature point to an unresolved issue regarding the level of board involvement that is conducive to effective strategy formulation. This study aims to identify the levels of board involvement that are associated with highly effective and less effective strategy formulation. Research Findings: We examine the boards of 16 intergovernmental organizations by conducting an inductive fuzzy‐set qualitative comparative analysis to identify different levels of board involvement that are associated with highly effective and less effective strategy formulation. Our results illustrate that both active and less active board involvement are associated with highly effective strategy formulation, while an intermediate level of board involvement is associated with less effective strategy formulation. Theoretical Implications: This study contributes to the literature seeking to understand board involvement in the strategy process. We build a multi‐dimensional board involvement framework consisting of board dynamics, the use of director resources, and context. We use the information‐processing perspective to elucidate the relationship between different levels of board involvement and effective strategy formulation. Practitioner Implications: Our findings suggest that the optimal level of board involvement in strategy formulation depends on an organization's complexity, a factor which determines its information‐processing needs.